Clonal structure of Trypanosoma cruzi Colombian strain (biodeme Type III): biological, isoenzymic and histopathological analysis of seven isolated clones - Camandaroba Edson Luiz Paes; Campos Rozália Figueira; Magalhães Juracy Barbosa; Andrade Sonia G. (Sociedade Brasileira de Medicina Tropical (SBMT), 2001)
The clonal structure of the Colombian strain of Trypanosoma cruzi, biodeme Type III and zymodeme 1, was analyzed in order to characterize its populations and to establish its homogeneity or heterogeneity. Seven isolated clones presented the basic characteristics of Biodeme Type III, with the same patterns of parasitemic curves, tissue tropism to skeletal muscle and myocardium, high pathogenicity with extensive necrotic-inflammatory lesions from the 20th to 30th day of infection. The parental strain and its clones C1, C3, C4 and C6, determined the higher levels of parasitemia, 20 to 30 days of infection, with high mortality rate up to 30 days (79 to 100%); clones C2, C5 and C7 presented lower levels of parasitemia, with low mortality rates (7.6 to 23%). Isoenzymic patterns, characteristic of zymodeme 1, (Z1) were similar for the parental strain and its seven clones. Results point to a phenotypic homogeneity of the clones isolated from the Colombian strain and suggest the predominance of a principal clone, responsible for the biological behavior of the parental strain and clones.